FIQH PEREMPUAN (Analisis Gender dalam Fiqh Islam Konteks Keindonesiaan) - MUHAMMAD JUFRI (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2014)
Fiqh is conceptually an integral part of syari’ah, since the former is an interpretation of the latter. As an interpretation, fiqh is a sort of ijtihad. Therefore, fiqh an interpretation on all matters related to women—is concequently also an ijtihad, which is subject to any changes in accordance with the changes of social development. In this era, women should not only be active in domestic matters, but should also be active in social life. Whereas fiqh concerning domestic matters must hold the principle of mu’asyarah bi al-ma’ruf, it must hold the principle of equality between man and women when the social life is concerned.